Youth Engagement in Global Affairs: FPCI Goes to SMA Muhammadiyah 3 Jakarta - M Kamil Ghiffary Abdurrahman; Asyifa Rahman; Kayla Azalia Putri Rosano (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This article discusses the implementation of FPCI Goes to School (FGTS) 4.0, an educational outreach initiative conducted by the Foreign Policy Community of Indonesia (FPCI) Chapter UPN Veteran Jakarta, with the objective of increasing students’ awareness and understanding of international political dynamics. The initiative addresses the growing need for public literacy on global issues that often have indirect but significant effects on national and local communities, such as trade disruptions and inflation caused by geopolitical conflicts. Using the Russia-Ukraine war as the primary case study, this activity sought to explore how international events influence domestic realities, including the rising cost of grain-based products and the spread of digital propaganda. The program was held at Muhammadiyah 2 Senior High School Jakarta and employed a participatory method involving socialization sessions, group discussions, and pre-test and post-tests evaluations to measure knowledge gain and critical thinking. Findings show that students demonstrated a strong grasp of basic geopolitical knowledge (+90% correct identification) and high level of awareness regarding digital security practices (+95% relevant answers). Slightly lower comprehension was observed in questions requiring simple analytical reasoning about international politics. This activity concludes that early exposure to international political education, delivered through targeted civic engagement programs, is promising to cultivate for a more globally-aware and resilient future citizens.